(untitled) (Al-Qamar, 2024)
Every year, a report on global gender discrimination is presented by the World Economic Forum as part of a survey, the aim of which is to clarify the data of gender discrimination in different countries of the world. After knowing the problems, in the light of the Prophet’s biographical, the solution for women’s economic empowerment will be presented. In this research, inferential and descriptive methods (documentary studies) will be used. This study aims at investigating economic empowerment of Pakistani Woman through analyzing the data for the Pakistan that are included in the Global Gender Gap Reports for the years (2015-2022). Obstacles, such as societal, cultural, family restrictions, work environment or spouse and child related barriers will also be specifically examined. Similarly, a joint national plan between government and civil society organizations will also be discussed to remove misconceptions about women’s empowerment and promote their economic reality in the light of the Prophet’s biographical. Apart from this, there will be a discussion regarding promoting women’s self-confidence and coping with social and psychological pressures faced by women.